Improved noise performance of ultrathin YBCO Dayem bridge nanoSQUIDs. (16th November 2016) - Arpaia, R; Arzeo, M; Baghdadi, R; Trabaldo, E; Lombardi, F; Bauch, T
Abstract: We have fabricated YBa2 Cu3 O 7 − δ (YBCO) nano superconducting quantum interference devices (nanoSQUIDs), realized in Dayem bridge configuration, on films with thickness down to 10 nm. The devices, which have not been protected by a Au capping layer during the nanopatterning, show modulations of the critical current as a function of the externally applied magnetic field from 300 mK up to the critical temperature of the nanobridges. The absence of the Au shunting layer and the enhancement of the sheet resistance in ultrathin films lead to very large voltage modulations and transfer functions, which make these nanoSQUIDs highly sensitive devices. Indeed, by using bare YBCO nanostructures, we have revealed an upper limit for the intrinsic white flux noise level S Φ, w 1 / 2 < 450 n Φ 0 Hz − 1 / 2 .